2019
DOI: 10.1111/jbi.13529
|View full text |Cite
|
Sign up to set email alerts
|

Similar but different: Revealing the relative roles of species‐traits versus biome properties structuring genetic variation in South American marsh rats

Abstract: Aim Wetland habitats, and the ecological restrictions imposed by them, structure patterns of genetic variation in constituent taxa. As such, genetic variation may reflect properties of the specific biomes species inhabit, or shared life history traits among species may result in similar genetic structure. We evaluated these hypotheses jointly by quantifying the similarity of genetic structure in three South American marsh rat species (Holochilus), and test how genetic variation in each species relates to biome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 72 publications
(113 reference statements)
0
5
0
4
Order By: Relevance
“…In this study, we assessed the genetic variation of Abrothrix longipilis using information contained in sequences of the mitochondrial gene Cytb and a wide panel of SNPs. RNA-seq remains as a underutilized approach to acquire larger amounts of nuclear sequence data in sigmodontine studies (see Giorello et al, 2018 ; Prado et al, 2019 for the two so far available studies). In this sense, we are paving the way for the much needed transition to the genomic era of the study of South American rodents (see also Valdez et al, 2015 ; Giorello et al, 2018 ), as a way to deepen the understanding of the patterns and processes that underlie rodent diversity (see claims in this line in Lessa et al (2014) and D’Elía, Fabre & Lessa (2019) ).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we assessed the genetic variation of Abrothrix longipilis using information contained in sequences of the mitochondrial gene Cytb and a wide panel of SNPs. RNA-seq remains as a underutilized approach to acquire larger amounts of nuclear sequence data in sigmodontine studies (see Giorello et al, 2018 ; Prado et al, 2019 for the two so far available studies). In this sense, we are paving the way for the much needed transition to the genomic era of the study of South American rodents (see also Valdez et al, 2015 ; Giorello et al, 2018 ), as a way to deepen the understanding of the patterns and processes that underlie rodent diversity (see claims in this line in Lessa et al (2014) and D’Elía, Fabre & Lessa (2019) ).…”
Section: Discussionmentioning
confidence: 99%
“…This indicates that there are factors that were not explicitly tested in our study. It is possible that the association between gene and geography on a regional scale relates to variation in the historical stability of the South American wetlands (Prado et al, 2019). However, studies have shown little variation in precipitation (Cheng et al, 2013), temperature (Colinvaux et al, 1996) and vegetation (Häggi et al, 2017) since the last glacial maximum (Pleistocene) in the Western Amazon.…”
Section: Discussionmentioning
confidence: 99%
“…The following genetic diversity metrics were calculated for each GC identified in each species: expected heterozygosity (HE EXP ), nucleotide diversity ( π ), and inbreeding coefficient ( F IS ), using the Query function available in “r2vcftools” 0.0.0.9 (Pope, 2020). Tests of significant differences in diversity values (among species and among GCs) were assessed with Tukey's test using Query function as well (see Prado et al, 2019). In addition, F ST (SNP‐based F ‐statistics) was used to measure genetic differentiation between GCs using the gl.fst.pop function in “dartR” 1.9.9.1 (Gruber & Georges, 2019) with 100 bootstraps.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations